Предмет: Алгебра,
автор: blackdayyes
Производные функций
Решение
Приложения:
Ответы
Автор ответа:
0
1)y=e^(x^2+sinx)
y'=e^(x^2+sinx)*(x^2+sinx)'=(2x+cosx)*e^(x^2+sinx)
2)y=x*e^(x^2)
y'=2x^2*e^(x^2)+e^(x^2)
y'(-1)=2*e+e=3e
y'=e^(x^2+sinx)*(x^2+sinx)'=(2x+cosx)*e^(x^2+sinx)
2)y=x*e^(x^2)
y'=2x^2*e^(x^2)+e^(x^2)
y'(-1)=2*e+e=3e
Похожие вопросы
Предмет: Физика,
автор: annmelnyk2008
Предмет: Математика,
автор: Аноним
Предмет: Английский язык,
автор: krisbablov
Предмет: Математика,
автор: yana138
Предмет: География,
автор: gjook